A multifactorial comparison of Australian youth soccer players' performance characteristics. Issue 1 (February 2020) - Bennett, Kyle JM; Novak, Andrew R; Pluss, Matthew A; Coutts, Aaron J; Fransen, Job
The current study aimed to investigate the performance characteristics that discriminate Australian youth soccer players according to their academy status. A total of 165 youth soccer players participated in this study and were sub-divided into either an early adolescence ( n = 92, age = 13.0 ± 0.6 years) or mid-adolescence ( n = 73 age = 14.8 ± 0.6 years) group. Players completed multifactorial assessments of anthropometry, motor competence, physical fitness, decision-making and psychological traits. Statistical significance was set at p ≤ 0.05. Multivariate analysis of variance identified dynamic balancing ability (both age groups), object manipulation (mid-adolescence), lateral jumping ability (both age groups), linear speed over 5 m (both age groups), change of direction skill (mid-adolescence), intermittent aerobic endurance (mid-adolescence) and total response time on a decision-making assessment (early adolescence) to discriminate academy status. Interestingly, a binomial logistical regression showed that a 0.1 s decrease in sprint time (i.e. running faster) increased the odds of a player belonging to a tier one academy by 19% and 47% for early and mid-adolescent players, respectively. Overall, performance in the motor competence and physical fitness assessments were in favour of the tier one academy players. These findings are indicative of a potential selection bias in the Australian talent pool or a training effect whereby tier one academy programmes emphasise the development of physical attributes. However, future research is required to further substantiate this in a larger sample of youth soccer players from other playing regions within Australia.